2005
DOI: 10.1007/s10875-005-2819-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Type 1 and Type 2 Cytokines in Antiviral Memory T Helper Function Among Women Coinfected with HIV and HCV

Abstract: Bias in cytokine responses has been proposed as a contributing mechanism to pathogenesis in persistent HIV or hepatitis C virus (HCV) infections. We investigated whether coinfection with HCV modifies the profile of antigen-specific cytokine secretion in women persistently infected with HIV compared to women with single HIV or HCV infection. The T helper response to HIV, HCV and cytomegalovirus (CMV) as a positive viral control was dominated by type 1 cytokines ( interleukin-[IL] 2, interferon-[IFN] γ and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…The levels of IL‐4 and IFN‐γ mRNA correlated with each other and with IL‐5 and IL‐4δ2 mRNA levels after anti‐CD3 stimulation, where IL‐5 mRNA levels were the best predictor of IFN‐γ mRNA levels after stimulation with anti‐CD3 ( P = 0·006). This is consistent with a positive correlation between the levels of T1 cytokines [IL‐2 plus IFN‐γ and tumour necrosis factor‐α (TNF‐α)] and T2 cytokines (IL‐4, IL‐5 and IL‐10) described in HIV‐ and HCV‐infected women, 30 and contrasts with active tuberculosis and asthma where there is excess IL‐4 mRNA relative to IL‐4δ2 or IFN‐γ 14,18 , 31 . Excess IL‐4δ2 has been linked with inhibition of IL‐4‐mediated B‐cell activation, 32 which provides an explanation for the association between a high IL‐4/IL‐4δ2 ratio and elevated IgE in asthmatics 31 .…”
Section: Discussionsupporting
confidence: 82%
“…The levels of IL‐4 and IFN‐γ mRNA correlated with each other and with IL‐5 and IL‐4δ2 mRNA levels after anti‐CD3 stimulation, where IL‐5 mRNA levels were the best predictor of IFN‐γ mRNA levels after stimulation with anti‐CD3 ( P = 0·006). This is consistent with a positive correlation between the levels of T1 cytokines [IL‐2 plus IFN‐γ and tumour necrosis factor‐α (TNF‐α)] and T2 cytokines (IL‐4, IL‐5 and IL‐10) described in HIV‐ and HCV‐infected women, 30 and contrasts with active tuberculosis and asthma where there is excess IL‐4 mRNA relative to IL‐4δ2 or IFN‐γ 14,18 , 31 . Excess IL‐4δ2 has been linked with inhibition of IL‐4‐mediated B‐cell activation, 32 which provides an explanation for the association between a high IL‐4/IL‐4δ2 ratio and elevated IgE in asthmatics 31 .…”
Section: Discussionsupporting
confidence: 82%
“…A recent report indicated that T helper responses are impaired in coinfected patients to a greater extent than monoinfected patients, as measured by effector function responses [37]. Therefore, HCV infection may lead to additional functional impairments without altering the number of such cells.…”
Section: Discussionmentioning
confidence: 99%
“…In human immunodeficiency virus (HIV)‐infected individuals, HCV co‐infection appears linked to increased morbidity and mortality [5–7]. We and others have previously reported more extensive T helper cell dysfunction in patients with HIV / HCV co‐infection compared with individuals with either HIV or HCV mono‐infection [8,9]. Although reduced CD4 cell counts in HIV‐infected individuals have a significant impact on immune function, emerging investigations suggest that additional levels of dysfunction linked to HCV may also exist.…”
Section: Introductionmentioning
confidence: 99%